The Difficulties of Elementary School Teacher in Developing Thematic Learning Tools for the Merdeka Curriculum - Galuh Anggita Damayanti; Muhroji Muhroji (Jurnal Kependidikan: Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran dan Pembelajaran, 2022)
This study aims to; (1) describe the understanding and readiness of teachers in developing learning instruments; (2) identify the difficulties and problems faced by teachers in the development of learning instrument; and (3) reveal the means made by teachers in overcoming the problems of developing thematic learning instrument for the Merdeka curriculum. The method in this study employed descriptive with a qualitative approach. The subjects were 12 homeroom teachers at SD N 1 Kaligentong and SD N 2 Jetis in Boyolali Regency, Central Java Province. The data collection techniques were using observation and interviews. The data were analyzed using an interactive model. The results of this study showed (1) teachers still lack an understanding of the development of thematic learning instrument that is in accordance with the regulation (2) the difficulties of teachers in compiling thematic learning instrument: developing essential competencies into HOTS indicators according to Bloom’s taxonomy, formulating learning objectives that contained ABCD components, the comprehensive application of the TPACK context in the learning material has not been maximized, determining learning strategies and methods that apply 21st century proficiency, limitations of IT-based media, creating questions that implement higher-order thinking skills (3) the means made by teachers to overcome the problems of developing thematic learning instrument for the Merdeka curriculum are by compiling together with the teacher working group, attending training, always trying to apply new strategies, and looking for references on the internet.